HUBUNGAN PERSEPSI MAHASISWA TERHADAP BANK SYARI’AH DENGAN MINAT MENJADI NASABAH - Kusuma, Maulana W.; Mulyadi, Acep (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2015)
The aim of this article is to know about correlation between student perception of the sbari?a banking and interesting to becoming customer. This study htc a quantitative research using the survey method and the correlation approach conducted on sixth semester student at UNISMA Bekasi by the number of students as many as944students. While the sample in this study as many as 90 students and taken by random sampling Results from this research is that there is a positive and significant relationship between students'perceptions of Islamic banks with interest as a customer with a 0.4S3 correlation test values 0.05 and regresiy - 11.353 + 0,36thx. 22.731 F-test with a significance level of0.000 below 0.05 And according to test results determinant coefficient 0.453, indicating that interest in becoming customers contributed 20.596 from the perception of Islamic banks. It can be concluded that the hypothesis that there is a relationship between students? perceptions of Islamic banks with a customer interest received or significant